Rethinking global democracy in Brazil - Fraundorfer, Markus, 1983- (Rowman & Littlefield International Ltd, 2018)
This book opens up contemporary and novel practices of Brazil's democracy for examination, including responses to global food security, the purchase of drugs, open democracy and internet governance.